Atherosclerosis associated pathways are upregulated in stenotic aortic valves from patients with severe concomitant coronary artery disease. (14th October 2021) - Plunde, O; Sarajlic, P; Franco-Cereceda, A; Back, M
Abstract: : Aortic valve stenosis (AVS) share pathobiology and risk factors with atherosclerosis. However, medical treatment effective against atherosclerosis lack ability to halt the progression of AVS. The aims of this study were to (i) determine the prevalence of coronary artery disease (CAD) in surgical AVS patients and (ii) to establish predictors of CAD in AVS patients and (iii) to identify differential aortic valve transcriptomic profiles depending on concomitant CAD. The study cohort consisted of 256 consecutive AVS patients with surgically verified tricuspid aortic valves, of which 74 aortic valves were collected. CAD defined as coronary artery stenosis requiring concomitant bypass surgery or previous acute coronary syndrome or percutaneous coronary intervention Transcriptomic data were obtained from microarray analysis of tissues from three different stages of AVS process (healthy, intermediate, and calcified tissue). All comparisons were sex and tissue adjusted. Non-coding probes were removed and a variance filter was applied prior to analysis which yielded 5121 genes. The prevalence of CAD in AVS was 49%. A logistic regression model revealed male sex, claudication, diabetes and current smoking as significant predictors of CAD when age, sex, peak transaortic velocity, hsCRP, eGFR and BMI were held constant. 28 genes were significantly (q<0.05) differentially expressed when aortic valves from patients with (n=43) and without (n=31) CAD were compared. A comparison of patients with concomitant multi vessel disease (2–3 affected vessel territories, n=20) and patients without CAD or single vessel disease (n=54) revealed 189 significantly expressed genes and an optimal visual separation on heatmap (Figure 2). Active-subnetwork-oriented-enrichment analysis identified upregulated aortic valve atherosclerosis associated pathways in multi vessel disease patients related to reactive oxygen species and cytokine signaling. This study provides a novel observation of differential aortic valve gene expression profile depending on concomitant severe CAD. The results revealed that patients with concomitant severe CAD exhibited underlying atherosclerosis-related mechanisms to their aortic valve disease. Therefore, future precision medicine against AVS may be facilitated by assessing concomitant CAD. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Karolinska Institute - Clinical Science Training ProgrammeSwedish Heart Lung Foundation